Methods of Knowledge Construction in Theravada Buddhist Philosophy - Kittipalo, Phra Satawat; (Charoen Khangkham), Phra Udomvajiramedhi; Khammuangsaen, Boonruam; Krongcheep, Siriporn; Ponsen, Kitsuchin (Journal of Dhamma for Life, 2025)
This article aims to study (1) The process of knowledge construction in Theravāda Buddhist philosophy and (2) The application of Buddhist principles in the development of knowledge. The study found that knowledge construction in Theravāda Buddhist philosophy is fundamentally based on the Threefold Training: Sīla (morality), Samādhi (concentration), and Paññā (wisdom). The study of the Tipiṭaka and its commentaries serves as a crucial source of knowledge. Additionally, the principle of Yoniso Manasikāra, or wise reflection, plays a significant role in fostering accurate understanding. Meditation practices, including both Samatha and Vipassanā, contribute significantly to the development of wisdom and insight into the nature of reality. This process enables practitioners to attain the ultimate truth and apply Buddhist principles in daily life. Regarding the application of Buddhist principles, the Four Noble Truths provide a systematic framework for analyzing and resolving problems through the examination of Dukkha (suffering), Samudaya (cause of suffering), Nirodha (cessation of suffering), and Magga (the path to cessation). Additionally, the principle of Paṭiccasamuppāda (dependent origination) enhances the understanding of causality and interdependent factors, promoting holistic knowledge development. The integration of study and practice is thus essential for deepening knowledge and ensuring its practical application. The combination of scholarly study, critical reflection, and systematic practice forms a vital process that supports the development of wisdom and understanding of the ultimate reality as it truly is.